Meroterpenoids with diverse ring systems and dioxolanone-type secondary metabolites from Phyllosticta capitalensis and their phytotoxic activity. Issue 33 (16th August 2019) - Ma, Kai-Liang; Wei, Wen-Jun; Li, Hang-Ying; Song, Qiu-Yan; Dong, Shi-Hui; Gao, Kun
Abstract: Twenty meroterpenoids with diverse ring systems including five new ones (1, 2, 5, 6, and15 ), together with two new (23 and24 ) and two known dioxolanone-type secondary metabolites were isolated from Phyllosticta capitalensis, an endophytic fungus from Cephalotaxus fortunei Hook. Compound1 was the first example with a 9, 14- seco ring A and a five-membered ring B in guignardone derivatives. Compound2 represented a novel guignardone derivative possessing a 5/7/6/5 ring system with CH2 -7 attached to C-4 rather than C-6 in ring D. The structures of all new compounds were elucidated using spectroscopic data analyses and electronic circular dichroism comparison. The phytotoxic effects of compounds1 – 24 on Lactuca sativa and Lolium perenne were evaluated. Compound22 showed inhibition activity on the shoots growth of L. sativa and L. perenne, as well as the roots growth of L. perenne. Graphical abstract: Image 1 Highlights: Isolation of five new guignardone derivatives and two new dioxolanone-type secondary metabolites from Phyllosticta capitalensis . Compound1 represented the first guignardone derivative possessing a bicyclic skeleton. Compound2 was a 5/7/6/5 ring system with CH2 -7 attached to C-4 in ring D. Compound5 was an infrequent guignardone derivative with a 5/6/6/5 ring system. Compound6 possessed an additional five carbons in chemical structure.